2011
DOI: 10.1088/0963-0252/20/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hollow cathode discharge plasma configurations

Abstract: Hollow cathodes are used in plasma contactor and electric propulsion devices to provide electrons for sustaining plasma discharges. Based on previous cathode life tests where erosion was observed on hollow cathode assembly components, it is desirable to understand the plasma flow field downstream of hollow cathodes. Plasma flow field measurements are presented herein for hollow cathode generated plasmas using both local and remotely located plasma diagnostics. Two cathode discharges are presented: 1) an open, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…Low frequency mode (7)(8)(9)(10)(11)(12) From the observations in Sec. III, we summarize the characteristics of the fluctuations in the normalized light intensity at 7-12 kHz:…”
Section: Interpretation Of Experimentally Observed Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency mode (7)(8)(9)(10)(11)(12) From the observations in Sec. III, we summarize the characteristics of the fluctuations in the normalized light intensity at 7-12 kHz:…”
Section: Interpretation Of Experimentally Observed Modesmentioning
confidence: 99%
“…4,5 While the erosionless steady state that results from magnetic shielding modifications is now well-understood, the impact of the MS upgrade on the transients in the thruster remains unclear. This is an important, unresolved question in light of the effect oscillations have been proposed to have on processes such as cathode erosion [6][7][8] and anomalous transport. [9][10][11][12][13][14][15][16] Moreover, with new missions enabled by MS technology calling for higher specific impulse and power over longer timescales, 17,18 there is a need for high-fidelity models for thruster performance.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the success the authors found in using the IAT collisionality to capture a number of experimentally observed trends, Mikellides et al noted that the incorporation of this effect into their models was based on conjecture: There was no experimental confirmation of the IAT. To be sure, acoustic modes have been proposed to explain some of the salient trends in the observed frequency spectra of probes inserted into hollow cathode plumes [22,23], but the acoustic nature of these waves has never been directly measured. This lack of experimental confirmation brings a number of questions to mind about the role of the IAT in the operation of hollow cathodes: Does the IAT even exist in the plasma plume, and if so, how does it depend on operating conditions?…”
Section: Introductionmentioning
confidence: 99%
“…3 Keeper erosion, on the other hand, is still considered anomalous. This is because keeper sputtering results from impact by ions from the cathode plume with energies that far exceed the cathode discharge voltage, [4][5][6][7][8][9][10][11] yet there is no classical reason why such high energy ions should exist. The erosion from these anomalous ions is becoming an increasingly important concern in light of new NASA programs that are calling for higher power electric propulsion missions with extended duration.…”
Section: Introductionmentioning
confidence: 99%